2021
DOI: 10.21608/ejchem.2021.55291.3162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of follicular fluid paraoxonase activity with pregnancy outcomes in women undergoing IVF/ICSI

Abstract: The search for a reliable marker to predict pregnancy success is not yet identified. This study aims to evaluate paraoxonase activities (PON1) in follicular fluid (FF) and their correlation with oocyte yield, fertilization, and clinical pregnancy (CP). Methods: The study included 99 women aged 22-37 years old who were undergoing IVF/ICSI, were divided into fertile, which represents the control group consisting of 25 participants, and the infertile group, which was subdivided into 21 patients with PCOS, 26 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The hydrolytic lactonase, arylesterase, and paraoxonase activities of PON1 are all inactivated under oxidative stress, and epidemiological evidence shows that low serum PON1 activity is associated with many pathological diseases. 11,29 Our study was in contract with a study by Azizi et al 30 who found significant lower PON1 activity in both that indicates the presence of oxidative stress. The fact that AOPP increased could be attributed to metabolic changes such as being overweight, obesity, and hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 80%
“…The hydrolytic lactonase, arylesterase, and paraoxonase activities of PON1 are all inactivated under oxidative stress, and epidemiological evidence shows that low serum PON1 activity is associated with many pathological diseases. 11,29 Our study was in contract with a study by Azizi et al 30 who found significant lower PON1 activity in both that indicates the presence of oxidative stress. The fact that AOPP increased could be attributed to metabolic changes such as being overweight, obesity, and hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 80%